Creole : The History and Legacy of Louisiana's Free People of Color - Kein, Sybil (Book collections on Project MUSE., 2000)
"In her introduction, Sybil Kein immediately addresses perhaps the book's most important - and controversial - question: who are the Creoles? The answer is not clear-cut. Of European, African, or Caribbean mixed descent, they are a people of color and Francophone dialect native to south Lousiana; and though their history dates from the late 1600s, they have been neglected in the literature. Creole is a project that both defines and celebrates this ethnic identity. In fifteen essays, writers intimately involved with their subject explore the vibrant yet marginalized culture of the Creole people across time - their language, literature, religion, art, food, music, folklore, professions, customs, and social barriers."--Jacket